Respuesta :

[tex]\huge{\color{red}{\fbox{\textsf{\textbf{Answer}}}}} [/tex]

-1

Step-by-step explanation:

[tex] \sf \sqrt{7 - 3z} = 3 + cz \\ \\ \sf z = 2 [/tex]

We will just substitute the value of z in the equation

[tex] \sf \implies \sqrt{7 - 3(2)} = 3 + c(2) \\ \\ \sf \implies \sqrt{7 - 6} = 3 + 2c \\ \\ \sf \implies \sqrt{1} = 3 + 2c \\ \\ \sf \implies 1 = 3 + 2c \\ \\ \sf \implies 1 - 3 = 2c \\ \\ \sf \implies - 2 = 2c \\ \\ \sf \implies \frac{ - 2}{2} = c \\ \\ \sf \implies \large \red{ \mathfrak{ - 1 = c}}[/tex]

ACCESS MORE